Protective Mechanism of Humanin Against Oxidative Stress in Aging-Related Cardiovascular Diseases - Cai, He; Liu, Yunxia; Men, Hongbo; Zheng, Yang (Frontiers in Endocrinology, 2021)
Physiological reactive oxygen species (ROS) are important regulators of intercellular signal transduction. Oxidative and antioxidation systems maintain a dynamic balance under physiological conditions. Increases in ROS levels destroy the dynamic balance, leading to oxidative stress damage. Oxidative stress is involved in the pathogenesis of aging-related cardiovascular diseases (ACVD), such as atherosclerosis, myocardial infarction, and heart failure, by contributing to apoptosis, hypertrophy, and fibrosis. Oxidative phosphorylation in mitochondria is the main source of ROS. Increasing evidence demonstrates the relationship between ACVD and Humanin (HN), an endogenous peptide encoded by mitochondrial DNA. HN protects cardiomyocytes, endothelial cells, and fibroblasts from oxidative stress, highlighting its protective role in atherosclerosis, ischemia-reperfusion injury, and heart failure. Herein, we reviewed the signaling pathways associated with the HN effects on redox signals, including Kelch-like ECH-associated protein 1 (Keap1)/nuclear factor erythroid 2-related factor 2 (Nrf2), chaperone-mediated autophagy (CMA), c-jun NH2 terminal kinase (JNK)/p38 mitogen-activated protein kinase (p38 MAPK), adenosine monophosphate-activated protein kinase (AMPK), and phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt)-Janus kinase 2 (JAK2)/signal transducer and activator of transcription 3 (STAT3). Furthermore, we discussed the relationship among HN, redox signaling pathways, and ACVD. Finally, we propose that HN may be a candidate drug for ACVD.